Community Empowerment through Mung Bean Sprouts Production Training Program - Sinaga, Ayu Oshin Yap; Maretta, Gres; Darmawan, Andy; Marpaung, David Septian Sumanto; Khusnul, Ramadhan; Handayani, Sri Astuti Fiteri (TeknoKreatif: Jurnal Pengabdian kepada Masyarakat, 2021)
As one important crop, especially in Asia, mung bean sprouts (Vigna radiata L.) offers many benefit and profit for those who able to produce it properly. In Kebun Jati village, such kind of commodities will very help for either self-consumption or business. However, the unknown knowledge and experience in production process often results on broken mung bean sprouts. Here, the simply technique, materials and tools was introduced to society in Kebun Jati village through community empowerment with motivation, training and accompaniment. The 10 total participant joined in this activity was motivated about benefit and profit of mung bean sprouts. Besides, participant was also trained how to produce mung bean sprouts properly. The significant improvement of knowledge was found on methods of mung bean sprouts production aspect, by 90% of participant becomes understood. Further accompaniment to transform raw materials of mung bean sprouts become useful product will improve the economic value.